Loss of Arabidopsis β-COP Function Affects Golgi Structure, Plant Growth and Tolerance to Salt Stress - Sánchez-Simarro, Judit; Bernat-Silvestre, César; Gimeno-Ferrer, Fátima; Selvi-Martínez, Pilar; Montero-Pau, Javier; Aniento, Fernando; Marcote, María Jesús (Frontiers in Plant Science, 2020)
The early secretory pathway involves bidirectional transport between the endoplasmic reticulum (ER) and the Golgi apparatus and is mediated by coat protein complex I (COPI)-coated and coat protein complex II (COPII)-coated vesicles. COPII vesicles are involved in ER to Golgi transport meanwhile COPI vesicles mediate intra-Golgi transport and retrograde transport from the Golgi apparatus to the ER. The key component of COPI vesicles is the coatomer complex, that is composed of seven subunits (α/β/β’/γ/δ/ε/ζ). In Arabidopsis two genes coding for the beta-COP subunit have been identified, which are the result of recent tandem duplication. Here we have used a loss-of-function approach to study the function of β-COP. The results we have obtained suggest that β-COP is required for plant growth and salt tolerance. In addition, β-COP function seems to be required for maintaining the structure of the Golgi apparatus.